Professor Jerzy KAPELEWSKI - KOZACZKA, Eugeniusz (Archives of Acoustics, 2015)
Professor Jerzy Kapelewski – a distinguished academic teacher, specialist in the field of theoretical physics, electronics and acoustics passed away on 22 March, 2015. Born in Warsaw on 19 May, 1939, Prof. Jerzy Kapelewski, completed a study in physics at Warsaw University in 1963. His master’s thesis was distinguished with the First Award of the Rector of Warsaw University. After a short period of work at Warsaw University he was drafted for military service at Military University of Technology, where he began to work in a team of physicists headed by Prof. Sylwester Kaliski. In 1973 he defended his doctoral dissertation under the supervision of Prof. Sylwester Kaliski. He received a grant from the Polish Academy of Sciences in support of his work towards a postdoctoral degree, and in 1981 he won the First Award of the Rector of MUT for the Best Postdoctoral Dissertation of the Year. He received the title of professor in technical sciences in 1990. For his scientific, didactic and organizational achievements Professor Kapelewski received many awards, among others the Award of the Department IV of the Polish Academy of Sciences and Awards of the Minister of Science and Higher Education, Minister of National Defense, and Awards of the Rector of the Military University of Technology, several times. He was also conferred numerous decorations, including Commander’s Cross of the Order of Polonia Restituta, Gold Cross of Merit, Silver Cross of Merit, Commission of National Education Medal and numerous service decorations. Prof. Kapelewski, as a full professor in the Faculty of Electronics, Military University of Technology (from 1991) significantly contributed to the development of the research potential. His unquestionable achievements made him a person recognizable and respected in communities of physicists and elec tronic specialists dealing with research on effect of me dia on various wave phenomena, both in acoustics and electromagnetism. In the academic community he was known for his special attention to maintaining high standards in education of students and conduct of research.